Effects of sprayer speed, spray distance, and nozzle arrangement angle on low-flow air-assisted spray deposition - Dai, Shiqun; Ou, Mingxiong; Du, Wentao; Yang, Xuejun; Dong, Xiang; Jiang, Li; Zhang, Tie; Ding, Suming; Jia, Weidong (Frontiers in Plant Science, 2023)
Air-assisted spraying technology is widely used in orchard sprayers to disturb canopy leaves and force droplets into the plant canopy to reduce droplet drift and increase spray penetration. A low-flow air-assisted sprayer was developed based on a self-designed air-assisted nozzle. The effects of the sprayer speed, spray distance, and nozzle arrangement angle on the deposit coverage, spray penetration, and deposit distribution were investigated in a vineyard by means of orthogonal tests. The optimal working conditions for the low-flow air-assisted sprayer working in the vineyard were determined as a sprayer speed of 0.65m/s, a spray distance of 0.9m, and a nozzle arrangement angle of 20°. The deposit coverages of the proximal canopy and intermediate canopy were 23.67% and 14.52%, respectively. The spray penetration was 0.3574. The variation coefficients of the deposit coverage of the proximal canopy and intermediate canopy, which indicate the uniformity of the deposition distribution, were 8.56% and 12.33%, respectively.